Analisis Kontribusi dan Efektivitas dalam PenerimaanePajakoRestoran, Pajak Hoteli dani Pajak Parkir terhadapi Pendapatan lAsli Daerahi(PAD) Kotal Kediri - Bhasthiar, Adhik; Srihastuti, Eni; Isnaniati, Siti (PARETO : Jurnal Riset Bisnis dan Manajemen, 2023)
Thisi researchi wasi conductedi with thel aim of knowingi the percentage contribution and effectiveness lof Restauranti Tax, Hotel iTax, andi Parkingi Tax lin thel City of Kediri. The datai analysisi techniquei usedi in thisi studyi is a quantitative descriptivel analysis. Thel steps of this research are calculating the leveli of contribution land effectiveness of restaurant tax revenue, hotel tax, and parking taxi on the regionali tax of the icity of Kediri from 2017 to 2021. Thei datal sourcel used in thisi study isi primaryi data with qualitative idata types and quantitative data taken directly fromi the company. The datanis in the formmof datacon the general history of PAD, PAD location, organizational structure, PAD vision and mission, employment, PAD operational activities, and PAD income reports for 2017-2021. From themresults of the calculation lanalysis, it showsi thatathe levelnof contributioni of restaurant tax, hotel itax, and parking taxoto Regional Tax, shows that in 2017-2021 the level of contribution has increased and decreased, but in general the trend has increased and lis ini theovery goodocategory withi a range of values 55.05%-85.05%. For theelevel of effectivenessmof irestaurant taxes, hotel taxes andaparking taxesi in 2017-2021 they are inothe very effectivencategory with a value of 83.76% -128.52%. it cani benconcluded thatewith the analysis of thealevel ofocontribution and the effectivenessi of restaurant tax revenue, hotelatax, and parking tax whether it has been effective or not.